Ocupação e agonia de um rio: a fecundidade “inglória” do Rio Claro no sul goiano - Oliveira, Franciane Araújo de (2018)
The watershed of Rio Claro, in the South of Goiás state, has been suffering significant compressions of human interference in nature. Even against the inconsistent situation of the river and its creeks, there are advancements in deforestations, irrigation in large scale by center pivots, the construction of dams, and the like. The way rivers are used reflects a model of relationship “society” and nature. Thus, we had as an objective to understand the process of “occupation” of Rio Claro supposing that the river is in agony. Therefore, we based ourselves in a qualitative and quantitative research, with shifts of literature reviews, field trips, interviews, participants’ observations, elaboration of maps of land use and water, register of images and the like. The defended thesis is that the interests of hegemonic groups in the watershed of Rio Claro, the “modern” agriculture and the hydropower sector, supported by the idea of ownership and control of the land and water by economic and political strategies, are held responsible for nature’s spoliation and socialize Rio Claro’s degradation, its creeks and life itself. We’ve verified that the beginning of the “occupation” process of the watershed of Rio Claro, from the second quarter of XIX century, was marked by a bloody war between the “pioneers, farm hunters” and the autochthonous of the region, the Kayapó (or Caiapó), which called themselves as “people of the hole/water place”, period in which the Kayapó were decimated in their native territory. There’s a continued primitive accumulation of lands in the watershed of Rio Claro and, currently, with the most cruel nuances, in the water spoliation and the exhaustion of the rivers. The social participation in deliberative spaces of water governance is still a chimera. The intimate relationship between Cerrado and the waters which irrigate this environment and divide themselves to different Brazilian regions collaborate to expose the strategic content of the geographic localization of the watershed of Rio Claro. The rage of hegemonic groups, under capitalist modes of production, transforms the natural wealth of Rio Claro into an “inglorious” fertility